EMPOWERMENT: THE SELF-PRESENTATION OF MOM PRENEUR ON INSTAGRAM - Nurbaity Nurbaity; Nurul Adha Kurniati (Lingua, 2022)
The analyzing of “The Self – Presentation of Mom Preneur on Instagram” is important to do because it considers how the self-presentation of Mompreneur is presented on Instagram through the lens of Goffman's Self Presentation, Kress Social Semiotics and van Leuwenn to discuss forms (markers) such as vectors, modalities, gaze, composition, perspective, line and color, as well as the way these forms are used to manifest meaning (significant) in sign making and MAK. Halliday's Systemic Functional Linguistics (SFL) focuses on ideational metafunctions, which have a decisive influence on the grammar of visual communication, by viewing images as a source for representation and thus displaying culturally generated meanings by analyzing images and the captions (text) they contain. post. This study aims to examine how Mompreneur Sheyla Taradia Habib @sheytaradia presents herself as a woman and mother by sharing practices and to find out what type of identity is described by Mrs. Mompreneur by investigating the meaning and value attached to images and captions (text). The results of this meaning show empowerment or empowering women, solid family, and authority. euwenn to discuss forms (markers) such as vectors, modalities, gaze, composition, perspective, line and color, as well as the way these forms are used to manifest meaning (significant) in sign making and MAK. Halliday's Systemic Functional Linguistics (SFL) focuses on ideational metafunctions, which have a decisive influence on the grammar of visual communication, by viewing images as a source for representation and thus displaying culturally generated meanings by analyzing images and the captions (text) they contain. post. This study aims to examine how Mompreneur Sheyla Taradia Habib @sheytaradia presents herself as a woman and mother by sharing practices and to find out what type of identity is described by Mrs. Mompreneur by investigating the meaning and value attached to images and captions (text). The results of this meaning show empowerment or empowering women, solid family, and authority.